A numerical study of two-particle settling in a thixotropic fluid using the immersed Boundary–Lattice Boltzmann method - Ferrari, Marco Aurelio (2021)
The settling of multiple particles in non-Newtonian fluids has great industrial importance. During the drilling operation in the oil and gas exploration, cuttings need to be removed from the borehole. The task is accomplished by a drilling fluid is used to transport these cuttings to the surface. The drilling fluid may have certain properties, that in the event of pumping stop, are capable of reducing the cuttings settling velocity and consequently reduce the build-up rate at the bottom of the borehole. The fluid’s ability to increase its viscosity and yield-stress is associated with thixotropy, a time-dependent property caused by the increasing structuring level of the particle present in the fluid. The studied problem then consists of spheres settling released from rest in an initially unstructured fluid which will be structured over time and increase its yield stress. Therefore have a reliable form to study the effects of fluid properties in this problem is important. The objetive is achieved by using a numerical model based on the lattice Boltzmann method coupled with the immersed boundary method, with its implementation in CUDA®/C++. The thixo-viscoplastic effect was implemented with the use of secondary particle distribution function, which was responsible for transporting the structural parameter in the flow. The particle dynamics had a six degree of freedom and the collision model used a soft-sphere approach. The numerical code was then verified in steps to assess each component of the numerical method. The results were considered satisfactory and allowed to proceed with the study of particles settling in a thixo-viscoplastic fluid. The first part of the study included evaluating of the settling behavior of a single sphere as a function of the Bingham numbers, breakdown, and build-up parameters. The data for terminal velocity then allowed the construction of numerical correlation as a function of the studied parameters. The second part of the study encompassed studying of the effects of the fluid properties in the interaction between the two settling particles. It was found different interactions regimes between the particles, where some cases did not perform the draft-kissing-tumbling process while others the particles continued to settle in conditions where a single particle would not.